Sejarah Pengembangan Lembaga Pendidikan Islam MA Mu’allimin Muhammadiyah Alabio di Kabupaten Hulu Sungai Utara - Syamsul Rahmi; Hatari; Hidayatul Husna (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to find out the history of the development of Islamic educational institutions at MA Mu’allimin Muammadiyah Alabio, where the purpose of history in this research is to investigate developments from the beginning to the present history establishment of an educational institution. The method used in this study is a qualitative method or field research, in which research is carried out by visiting the relevant educational institution in the Alabio area. The purpose of this study is to find out and analyze the early history of the establishment of the MA Mu’allimin Muhammadiyah Islamic education institution Alabio Hulu Sungai Utara, as well as find facts from the historical events of the development of the Islamic education institution MA Mu’allimin Muhammadiyah Alabio Hulu Sungai Utara.